2015
DOI: 10.1039/c5dt00169b
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilicity-dependent ruthenium N-heterocyclic carbene complexes as potential anticancer agents

Abstract: Five Ru(II)-N-heterocyclic carbenes (NHC) (1-5) were synthesized by reacting the appropriately substituted imidazolium chlorides with Ag2O, forming the NHC-silver chloride in situ followed by transmetalation with dimeric p-cymene ruthenium(II) dichloride. All the complexes were characterized by NMR and ESI-MS, and complex 1 was also characterized by single-crystal X-ray diffraction. The IC50 values of these five complexes were determined by the MTT-based assay on four human cancer cell lines, SKOV-3 (ovarian),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…The untethered ruthenium NHC complexes weres ynthesized by transferring the NHC from AgNHC generated in situ [38,39] from the NHC precursor (L) and silver oxide [38] in the dark to Ru in the dimer of dichloro(p-cymene)ruthenium(II) [40,41] (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…The untethered ruthenium NHC complexes weres ynthesized by transferring the NHC from AgNHC generated in situ [38,39] from the NHC precursor (L) and silver oxide [38] in the dark to Ru in the dimer of dichloro(p-cymene)ruthenium(II) [40,41] (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the cells exhibited shrinkage and became round. This indicated that complex 3a can induce apoptosis of the cancer cells . Finally, scratch‐wound cell migration assays of LoVo cells were conducted (Figure ).…”
Section: Resultsmentioning
confidence: 92%
“…In contrast, complex 3b , bearing the same NHC–Ru–( p ‐cymene) core, was less efficacious than either complex 3a or cisplatin in all tested cancer cells. The enhanced cytotoxicity activity of complex 3a may be attributed to the high lipophilicity substitution of mesityl at the position of imidazolylidene ring promoting cellular uptake . Several other Ru–NHCs, including Grubbs catalysts, have been evaluated for their anticancer properties .…”
Section: Resultsmentioning
confidence: 99%
“…The solid-state structures ( Figure 3) show piano stool geometry around the metal centres, with each metal bearing two chloride atoms, an NHC and either Cp* (2b) or p-cymene (6b). The M-Ccarbene bond lengths of 1.92(3) Å (2b) and 2.064(7) Å (6b) are relatively short when compared to other IrCp*(NHC)Cl2 and Ru(pcymene)(NHC)Cl2 complexes in the literature, 37,[41][42][43][44][45] which may be an effect of the carborane substituent causing the carbenic carbon to be more nucleophilic than other NHCs. Similarly to complex 3a, the Ir complex 2b underwent cyclometallation upon reaction with Ag2O in MeCN.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 97%